Priority areas for ecological restoration and reference sites in Chignahuapan-Zacatlan region - González Ovando, María Luisa; Plascencia Escalante, F. Ofelia; Martínez-Trinidad, Tomás (Instituto de Ecología, A.C., 2016)
Degradation of natural resources has generated the need for ecological restoration. It is therefore necessary to identify in a simple manner the areas to be restored and prioritize the activities. The main aim of this study was to use Multi-Criteria Evaluation to identify priority areas for ecological restoration in the Chignahuapan-Zacaltan region of Puebla, Mexico, and to use remote sensing to determine reference sites for restoration. An Analytic Hierarchy Process through a GIS environment was used to identify priorities for attention. Mapping Information of 12 environmental criteria was used, together with the knowledge of 21 experts in restoration, which was incorporated through pairwise comparison matrices. The reference sites were determined by the supervised classification of satellite images and the exclusion of areas that presented some form of disturbance. The results indicate that about 80% of the area was classified with a level of priority for restoration. However, only 0.8% was classified as maximum priority. On the other hand, the area with potential to serve as a reference within the study area is approximately 4753 hectares. With recognition of these areas to be restored and reference sites in the maps, the efficiency and planning for restoration will be improved.